Six month follow-up of two Bulk-fill composites in non-carious cervical lesions: Double blind randomized clinical trial - Patricio Vildósola; Jorge Nakouzi; Sara Rodriguez; Jenifer Reyes; Camila Conejeros (Universidad de Concepción., 2019)
Objective: To assess the six-month clinical outcome of restorations of non-carious cervical lesions (NCCL) with two composite resins: Bulk-Fill and nanohybrid resin. Materials and methods: Fifty-one patients, with three NCCLs each, were randomly allocated into three restoration groups: Tetric-N-Ceram Bulk-Fill (TB); Filtek Bulk-Fill (FB); y Filtek Z350XT (Z350). Adhesive techniques and restorative procedures were performed according to the manufacturers' instructions for the different materials. A 4mm increment was applied in TB and FB, and increments of ≤2mm depth were applied in Z350. Restorations were assessed by two calibrated examiners at baseline and at six months according to the FDI World Dental Federation guidelines (1: excellent, 2: acceptable, 3: sufficient, 4: unsatisfactory, 5: unacceptable) in Marginal Staining (MS), Fracture-Retention (FR), Marginal Adaptation (MA), Postoperative Sensitivity (S) and Caries (C). Wilcoxon test was used for the comparison between baseline and 6 months, and Kruskal-Wallis for the comparison of the three groups at six months (95% significance). Results: Forty-six patients with a total of 138 restorations attended a check-up at six months and were evaluated with excellent clinical outcome. In MS, 91.2% for Z350 and 97.8% for FB and TB; in FR, 97.8% for Z350 and 100% for FB and TB; in MA, 95.6% for Z350, 97.8% for FB and 100% for TN; in S, 95.6% for all three groups; and 100% for C. No statistically significant differences were found between the three groups nor in the comparison between the baseline and 6 months (p>0.05) Conclusion: No significant differences are observed between the three groups of resins in the parameters of MS, MA, S, FR and C regarding clinical outcome at six months.